ROLE OF THE SALESPERSON IN “TOTAL DESIGN” - Nelu DORLE (Challenges of the Knowledge Society)
Sales Management has known, during the last decades, a fulminating increase in the degree of complexity, enriching itself with new relationship strategies among the different components of the management system. These aim at new perspectives on the relationship between production and sale, between factory and market, and finally on the relationship between manufacturer and salesperson. The traditional view on designing a product is improved by means of the “Total Design” system, which targets a more ample perspective of the product and its fields of reference, in the sense that it gives greater importance to marketing and the requests of customers in the production design. And in this respect, the salesperson as a main link between the two economic spheres, gains a fundamental role.